2023
DOI: 10.3390/polym15061470
|View full text |Cite
|
Sign up to set email alerts
|

Facile One-Step Electrospinning Process to Prepare AgNPs-Loaded PLA and PLA/PEO Mats with Antibacterial Activity

Abstract: Nanofibers can play an important role in developing new kinds of medical applications. Poly(lactic acid) (PLA) and PLA/poly(ethylene oxide) (PEO) antibacterial mats containing silver nanoparticles (AgNPs) were prepared by a simple one-step electrospinning method that allows AgNPs to be synthesized simultaneously with the preparation of the electrospinning solution. The electrospun nanofibers were characterized by scanning electron microscopy, transmission electron microscopy and thermogravimetry, while silver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…The surface zeta potential (ζ) of the scaffolds was investigated as a function of pH using the surface streaming potential. These results are consistent with the literature 21 and show a decrease in ζ values with increasing pH, caused by the pKa of chitosan amino groups that have an alkaline character ( Figure 6 ). A similar behavior was observed for the HEC-doped scaffolds.…”
Section: Resultssupporting
confidence: 93%
“…The surface zeta potential (ζ) of the scaffolds was investigated as a function of pH using the surface streaming potential. These results are consistent with the literature 21 and show a decrease in ζ values with increasing pH, caused by the pKa of chitosan amino groups that have an alkaline character ( Figure 6 ). A similar behavior was observed for the HEC-doped scaffolds.…”
Section: Resultssupporting
confidence: 93%
“…The silver release data agree well with those of Qian Y. et al (2019), who demonstrated that silver-modified/collagen-coated electrospun poly-lactic-co-glycolic acid (PLGA)/PCL scaffolds released silver over time, with a peak after 12–16 days [ 34 ]. Additionally, most of the results pertaining to the silver release were performed from electrospun fibers or membranes made of PCL; in this research, the authors revealed a tailored and progressive release of silver from these structures into the medium [ 35 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Allizond et al reported a one-step method for preparing electrospun nanofibers containing AgNPs from polylactic acid/polyethylene oxide (PLA/PEO). The experimental results showed that AgNP–PLA/PEO nanofibers effectively killed S. epidermidis and E. coli by rapidly releasing silver ions [ 156 ]. Spagnol et al modified cellulose whiskers (CWs) to produce carboxylated CWs (CWSAc) with carboxyl groups (-COO-), and then immersed them in a silver nitrate solution (AgNO 3 ) to synthesize AgNPs in situ and anchor AgNPs on the surface.…”
Section: Electrospun Nanofiber Scaffolds Loaded With Metal-based Nano...mentioning
confidence: 99%